Effect of flow path structure on solid/liquid separation under electric field - Tanaka, Takanori; Kato, Hiroki; Fujihara, Kenji; Jami, Mohammed Saedi; Iwata, Masashi (Elsevier Inc., 2015)
Electroosmosis is especially effective in removing liquid from a highly compressible difficult-to-filter solid/liquid mixture. The extent of solid/liquid separation depends on the electroosmotic pressure gradient (Epg) which is a combination of applied electric field, the surface charge density of solid particles and the flow path structure in the mixture. The larger the Epg value, the higher the solid content of the treated mixture. A theoretical equation of Epg for a capillary flow is derived from the Navier–Stokes equation, and its extensions to a flow through porous materials are examined by using experimental Epg values from constant-current electroosmotic dewatering (EOD), electroosmotic permeation (EOP) and electro-forced sedimentation (EFS) tests. It has been clarified that the specific hydrodynamic resistance α has the most effect on the Epg value. The larger the α value of the material, the larger its Epg value. Modifications to the existing theories were suggested to understand the effect of solid/liquid mixture concentration on the separation under electric field more precisely.